General practitioners: Between integration and co-location. The case of primary care centers in Tuscany, Italy. (February 2019) - Barsanti, Sara; Bonciani, Manila
Healthcare systems have followed several strategies aimed at integrating primary care services and professionals. Medical homes in the USA and Canada, and primary care centres across Europe have collocated general practitioners and other health and social professionals in the same building in order to boost coordination among services and the continuity of care for patients. However, in the literature, the impact of co-location on primary care has led to controversial results. This article analyses the possible benefits of the co-location of services in primary care focusing on the Italian model of primary care centres (Case della Salute) in terms of general practitioners' perception. We used the results of a web survey of general practitioners in Tuscany to compare the experiences and satisfaction of those general practitioners involved and not involved in a primary care centre, performed a MONAVA and ANOVA analysis. Our case study highlights the positive impact of co-location on the integration of professionals, especially with nurses and social workers, and on organizational integration, in terms of frequency of meeting to discuss about quality of care. Conversely, no significant differences were found in terms of either clinical or system integration. Furthermore, the collaboration with specialists is still weak. Considering the general practitioners' perspective in terms of experience and satisfaction towards primary care, co-location strategies is a necessary step in order to facilitate the collaboration among professionals and to prevent unintended consequences in terms of an even possible isolation of primary care as an involuntary 'disintegration of the integration'.